Uptake And Availability Of Potassium And Nitrogen In Wheat As Influenced By Their Split Application Under Temperate Conditions Of Kashmir (Applied Biological Research, 2017)
An experiment was conducted at University Research Farm, SKUAST-K,  Shalimar, Srinagar (J&K) to evaluate the effect of split application of  potassium and nitrogen on their uptake and availability in wheat. The  experiment was laid in a split plot design with 15 treatment combinations, viz.,  3 levels of potassium (K) @ 30 kg ha-1[K1: 100% K as basal dose – [recommended fertilizer dose (RFP)]; K2: split 50:50; K3: split 25:75] and 5 of  nitrogen (N) @ 120 kg ha-1[N1: 50:25:25 (RFP); N2: 25:75, N3: 25:50:25, N4:  50:50 and N5: 0:75:25]. The application of K in equal splits (basal + active  tillering) improved grain yield by 10.6 and 11.6%, straw yield by 11.6 and  13.4%, K uptake by 17.2 and 18.8% and N uptake by 16.4 and 17.2% during  2013-14 and 2014-15, respectively, over RFP. The available K decreased  steadily with recommended application but maintained its status quo when  applied in split dose. The available N in soil maintained status quo with RFP; however, it showed decline when K was applied in splits. The N application in  25:50:25 ratios (basal + active tillering + booting) enhanced grain yield, straw  yield and total K and N uptake during both the years. Also, K and N content  in soil decreased when N was applied in 3 splits as compared to 2 splits, where  it maintained status quo after harvest of 2nd year crop. This indicates there  may be need to increase N dose in order to maintain the N status of soil.
Keywords: Available soil nutrient; nutrient uptake; split application; wheat; yield